Nitrate reductase-mediated synthesis of silver nanoparticles from AgNO3 - Kumar, S. Anil; Abyaneh, Majid Kazemian; Gosavi, S. W.; Kulkarni, Sulabha K.; Pasricha, Renu; Ahmad, Absar; Khan, Mohammad Islam (Biotechnology Letters, 2007)
Synthesis of silver nanoparticles using alpha-NADPH-dependent nitrate reductase and phytochelatin in vitro has been demonstrated for the first time. The silver ions were reduced in the presence of nitrate reductase, leading to the formation of a stable silver hydrosol 10-25 nm diam. and stabilized by the capping peptide. The nanoparticles were characterized by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and UV-Vis absorption. These studies will help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: Capping Peptide; enzymatic method; nitrate reductase; silver nanoparticles